Implementasi Sistem Informasi Undangan Digital Berbasis WEB - Arif Bakti Nugraha; Aren Kurnia (FKOM UNIKU, 2024)
A wedding invitation is a letter in the form of a card asking the recipient to attend a wedding. But now, wedding invitations can also be distributed via social media in the form of a web which is commonly called digital invitations. This study discusses the registration process, inputting forms, package selection, and payment. In addition, there is an admin interface whose job is to manage transactions which include managing payments, and managing incoming orders in the form of user data that will be included in the invitation web design.